(untitled) (The Journal of Building and Land Development, 2026)
Climate change, such as global warming, has continuously affected freshwater quality, making it one of the most pressing global problems. The scenario is especially severe in low- and middle-income countries due to limited resources to identify pollutant sources and set targeted control measures. Dissolved Oxygen can respond quickly to climate (temperature)-driven water quality deterioration. However, Dissolved Oxygen use as a low-cost, rapid screening method for temperature-driven freshwater quality deterioration remains underexplored due to methodological complexities in isolating temperature effects from other Dissolved Oxygen stressors. This study developed a novel experimental setup in a controlled environment (laboratory), using deionized distilled water aerated with a medical-grade 100% pure oxygen to ascertain the temperature-driven Dissolved Oxygen dynamics, suppressing other confounding Dissolved Oxygen stressors. Linear and segmented regression analysis of Dissolved Oxygen against temperature rise revealed an average Dissolved Oxygen decrease of 0.103 mg/L per unit temperature. Also, Dissolved Oxygen decreased by 0.084 mg/l, 0.068 mg/l, and 0.262 mg/l per unit increase in temperature across temperature ranges of 8-22 ˚C, 23-35 ˚C, and 36-45 ˚C, respectively. It was recommended that the Dissolved Oxygen-temperature regression model should be integrated into rapid screening frameworks for climate-driven water-quality deterioration. The study aligns with SDG 6.3.2 and SDG 13 and contributes to knowledge through a novel experiment. Keywords: Distilled Water, Temperature, and Water Quality